Factors Associated with Neck Pain Among the Local Gamer Community in IndonesiaIntroduction: There has been a notable rise in smartphone usage among youth, with many exceeding 3 hours of screen time each day. This is a high-risk factor for suffering from n (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2024)
Introduction: There has been a notable rise in smartphone usage among youth, with many exceeding 3 hours of screen time each day. This is a high-risk factor for suffering from neck muscle fatigue due to the static posture of the cervical spine. Objective: This study is to determine factors associated with neck pain among the local gamer community in Indonesia. Methods: This study is multivariate predictive study with a cross-sectional approach to members of the AiMSTAR, one of the online gaming communities in Indonesia. The sample was selected using the total sampling technique. Data collection in this study used a questionnaire. Results: Based on the results of multivariate analysis, it was found that the frequency of smartphone use among gamers in the AiMSTAR community had a significant influence on the occurrence of neck pain, with a p-value of 0.002 (p < 0.05) and a six-fold increased risk compared to a usage frequency of less than 30 minutes (95% CI = 1.96–18.57). Conclusion: This study shows that the frequency of using smartphone is the most significant contributing factor to the occurrence of neck pain among the local online gaming community in Indonesia.